Solving Engineering Optimization Problems with the Simple Constrained Particle Swarm Optimizer - Cagnina, L.C.; Esquivel, S.C.; Coello, C.A.C. (Informatica)
Solving Engineering Optimization Problems with the Simple Constrained Particle Swarm Optimizer